Pengaruh Hasil Belajar Pendidikan Anti Korupsi dan Interaksi Sosial terhadap Integritas pada Mahasiswa PPKn Universitas Jambi Angkatan 2023 - Hidayat, Rahmat; Hajri, Priazki; Sariani, Dona (YASIN, 2025)
Integrity is a fundamental attitude that must be possessed by every individual, particularly by students of the 2023 cohort of the Civic Education (PPKn) program at Universitas Jambi, given their role as future leaders of the nation who are expected to uphold high moral and personal standards. This study aims to examine the influence of learning outcomes in anti-corruption education and social interaction on student integrity. A quantitative approach was employed using a survey method involving 95 respondents. Data were analyzed using inferential statistical techniques to test the relationships between variables. The results indicate that learning outcomes in anti-corruption education and social interaction significantly affect student integrity, with a significance value of 0.000 (p < 0.05). The combined influence of these two variables on integrity is 34.6%, while the remaining variance is attributed to factors beyond the scope of this study. These findings suggest that the better the learning outcomes in anti-corruption education and the more active the students' social interactions, the higher their level of integrity. The study highlights the importance of integrating anti-corruption values into the educational process and strengthening social interaction as strategic efforts to foster student character development rooted in integrity.